2007
DOI: 10.1002/ajmg.a.31673
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide linkage scan for cleft lip and cleft palate identifies a novel locus on 8p11‐23

Abstract: Isolated or nonsyndromic cleft lip and palate (NS CLP) is a complex disorder resulting from multiple genetic and environmental factors. NS CLP has a birth prevalence of 1 per 500 in the Philippines where large families provide an opportunity for gene localization. Genotyping of 392 microsatellite repeat markers at 10 cM intervals over the genome was performed by the Center for Inherited Disease Research (CIDR) on 220 Filipino families with 567 affected and 1,109 unaffected family members genotyped. Among the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 49 publications
4
32
0
3
Order By: Relevance
“…These signals are near to the 48 cM signal we previously reported [Riley et al, 2007] with a LOD score of 2.38 in 220 Filipino families. Fine mapping work also presented in Riley et al [2007] showed both linkage and association positive results for markers in FGFR1 and BAG4, while either linkage or association showed positive results for markers in SLC18A1, EPHX2, and FZD3. However, under a more strict criteria correcting for multiple testing, none of these results would be statistically significant.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…These signals are near to the 48 cM signal we previously reported [Riley et al, 2007] with a LOD score of 2.38 in 220 Filipino families. Fine mapping work also presented in Riley et al [2007] showed both linkage and association positive results for markers in FGFR1 and BAG4, while either linkage or association showed positive results for markers in SLC18A1, EPHX2, and FZD3. However, under a more strict criteria correcting for multiple testing, none of these results would be statistically significant.…”
Section: Discussionsupporting
confidence: 77%
“…Our preliminary study indicated three regions that yielded suggestive positive linkage results (LOD scores higher than 1.0) in 220 multiplex extended Filipino kindreds: 2p21, 6q23, and 8p21. The highest signal was in 8p11-23 (single point recessive LOD score =1.2 and multipoint recessive LOD score =2.3) and follow up studies with 271 families showed suggestive linkage disequilibrium results for FUT10, BAG4, and FGFR1 [Riley et al, 2007]. Even though this was a large study of 220 families (567 affected and 1,109 unaffected family members genotyped), the results were just modest.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Egfr, Bmp4, Bmpr1 and Folbp1) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Eight genome scans have identified regions that may potentially harbor NSCLP susceptibility genes (19)(20)(21)(22)(23)(24)(25). In 2000, Prescott et al (26) identified nine chromosomal regions that are associated with orofacial clefting in their Caucasian NSCLP sib-pair population.…”
Section: Introductionmentioning
confidence: 99%